2006
DOI: 10.1080/13869790600641905
|View full text |Cite
|
Sign up to set email alerts
|

Bad acts, blameworthy agents, and intentional actions: Some problems for juror impartiality

Abstract: In this paper, I first review some of the recent empirical work on the biasing effect that moral considerations have on folk ascriptions of intentional action. Then, I use Mark Alicke's affective model of blame attribution to explain this biasing effect. Finally, I discuss the relevance of this research-both philosophical and psychological-to the problem of the partiality of jury deliberation. After all, if the immorality of an action does affect folk ascriptions of intentionality, and all serious criminal off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
124
1
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(130 citation statements)
references
References 18 publications
3
124
1
2
Order By: Relevance
“…Certain scholars argue that the Knobe effect constitutes a bias, and that the folk use of intentionality is frequently distorted (Adams & Steadman, 2004;Alicke, 2008;Alicke & Rose, 2010;Nadelhoffer, 2004aNadelhoffer, , 2004bNadelhoffer, , 2006Sauer & Bates, 2013). In contrast to such views, several scholars have argued that the Knobe effect testifies to people's competence in intentionality ascriptions (cf.…”
Section: Competence V Bias Accountsmentioning
confidence: 99%
See 3 more Smart Citations
“…Certain scholars argue that the Knobe effect constitutes a bias, and that the folk use of intentionality is frequently distorted (Adams & Steadman, 2004;Alicke, 2008;Alicke & Rose, 2010;Nadelhoffer, 2004aNadelhoffer, , 2004bNadelhoffer, , 2006Sauer & Bates, 2013). In contrast to such views, several scholars have argued that the Knobe effect testifies to people's competence in intentionality ascriptions (cf.…”
Section: Competence V Bias Accountsmentioning
confidence: 99%
“…What is more, evidence by Nadelhoffer (2006) demonstrates that moral factors independent of outcome valence such as the character of the defendant and victim -certainly not among the 1 A worry: What drives the Knobe effect are differently valenced outcomes. But -one might argue -the distinction between positive and negative moral or normative valence is mute as regards legal matters, since the only outcomes of relevance are negative ones.…”
Section: Competence V Bias Accountsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to do this, we drew upon the so-called "Knobe Effect": Knobe (2003) found that the positiveness or negativeness 2 of sideeffects of actions influences people's assessment of whether those side-effects were brought about intentionally, and also that people are more willing to assign blame for negative side-effects of actions than they are to assign praise for positive side-effect of actions (see also Nadelhoffer 2005Nadelhoffer , 2006Knobe 2006;Nichols and Ulatowski 2007;Malle 2010;Cova 2015). Building upon this body of research, we aimed to answer the question whether a "Group Knobe Effect" (GKE) also obtains, i.e.…”
Section: Introductionmentioning
confidence: 99%